2012
DOI: 10.2319/071212-575.1
|View full text |Cite
|
Sign up to set email alerts
|

Labio-lingual root control of lower anterior teeth and canines obtained by active and passive self-ligating brackets

Abstract: A significant proclination was seen for the mandibular front teeth; the claimed third-order torque control of SL systems could not be demonstrated. Therefore, a considerable play between the wire and the brackets could be hypothesized, even more in relation to the passive than the active SL brackets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 27 publications
2
21
1
3
Order By: Relevance
“…Most studies have depicted mandibular incisor proclination in both groups with no statistical difference [Jiang and Fu, 2008;Scott et al, 2008;Pandis et al, 2010], once again indicating that the mechanism for relieving crowding involves incisor proclination and transverse expansion through tipping of posterior teeth, which is similar for conventional and self-ligating brackets. Also, another study using CBCT to compare the labiolingual inclination of mandibular incisors relative to the occlusal plane between active and passive self-ligating brackets confirmed a significant proclination of mandibular anterior teeth, thereby rejecting the claim of torque control by self-ligating systems [Cattaneo et al, 2013]. The meta-analysis including three of these studies showed that self-ligating brackets had 1.5 degrees less proclination that was statistically significant, although it may not be a clinically significant change [Chen et al, 2010].…”
Section: Discussionmentioning
confidence: 96%
“…Most studies have depicted mandibular incisor proclination in both groups with no statistical difference [Jiang and Fu, 2008;Scott et al, 2008;Pandis et al, 2010], once again indicating that the mechanism for relieving crowding involves incisor proclination and transverse expansion through tipping of posterior teeth, which is similar for conventional and self-ligating brackets. Also, another study using CBCT to compare the labiolingual inclination of mandibular incisors relative to the occlusal plane between active and passive self-ligating brackets confirmed a significant proclination of mandibular anterior teeth, thereby rejecting the claim of torque control by self-ligating systems [Cattaneo et al, 2013]. The meta-analysis including three of these studies showed that self-ligating brackets had 1.5 degrees less proclination that was statistically significant, although it may not be a clinically significant change [Chen et al, 2010].…”
Section: Discussionmentioning
confidence: 96%
“…While it is clear that CBCT scans can accurately capture the dentoalveolar complex in 3D, it is best to be selective about what cases may benefit from CBCT scans for assessing boundary conditions. 85,86 These include cases presenting with clinically noticeable thin alveolar bone phenotypes that may not tolerate significant labio-or buccolingual displacements (Figure 7); cases with pre-existing periodontal disease; cases requiring orthodontic tooth movements that extend beyond pre-treatment alveolar boundaries; and cases where a tooth may need to be translocated past another tooth or obstruction (Figure 8). Precise information on alveolar boundary conditions may also be helpful in treatment planning cases that require moving teeth close to the alveolar boundaries such as in borderline non-extraction cases or in situations where teeth are being decompensated, such as commonly is performed in orthognathic surgery cases.…”
Section: Utilization Of Cbct For Orthodontic Treatment Outcomes Diagmentioning
confidence: 99%
“…Al escoger entre los diferentes tipos de brackets auto-ligado activos o Pasivos, la evidencia nos muestra que hay una mayor variación entre la inclinación más pronunciada de los dientes anteriores después del tratamiento en el bracket autoligado pasivo. (19) Otro estudio que compara los diferentes tipos brackets auto-ligados como: Profile views of Time2™, In-Ovation R™, Speed™, and Damon3™, demostraron que el diseño del bracket auto-ligado (pasivo frente al activo) es la variable más importante al ser la responsable de la resistencia al movimiento generado (fricción), en los brackets pasivamente ligados se observó que hubo disminución en la fricción (Fig. 4); pero, esta disminución puede deberse por la falta del control en el sistema de ligadura por los brackets auto-ligados activamente.…”
Section: Brackets Auto-ligados Pasivos Vs Activosunclassified